1997
DOI: 10.1029/96jb03409
|View full text |Cite
|
Sign up to set email alerts
|

Cutting of the European continental lithosphere: Plasticity theory applied to the present Alpine collision

Abstract: Abstract. Presently active European Alpine collision has a history of more than 100 Myr convergence. We investigate the collisional contact problem of an apparently rigid African promontory (currently the Italy/Adria block (IAB)) steadily penetrating at 1 cm/yr, over at least the past 45 Myr, into the deformable European plate. We assume that neither continental subduction nor delamination occurs presently in the 300-km-wide contact zone enabling use of the indenter-indentee approach. A key parameter is the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The pre-Alpine earthquakes in NE Italy are mostly associated with a rough N-S compression, implying a sinistral strike slip kinematics along the Giudicarie system. This structural setting is consistent with the concept of an active northwards indentation of the Adria plate towards Europe (Bressan et al, 1998;Regenauer-Lieb and Petit, 1997;Renner and Slejko, 1994), as also confirmed by independent geodetic data (Caporali et al, 2003a) (Fig. 2b).…”
Section: Structural and Seismological Settings Of The Area And The Mesupporting
confidence: 89%
See 1 more Smart Citation
“…The pre-Alpine earthquakes in NE Italy are mostly associated with a rough N-S compression, implying a sinistral strike slip kinematics along the Giudicarie system. This structural setting is consistent with the concept of an active northwards indentation of the Adria plate towards Europe (Bressan et al, 1998;Regenauer-Lieb and Petit, 1997;Renner and Slejko, 1994), as also confirmed by independent geodetic data (Caporali et al, 2003a) (Fig. 2b).…”
Section: Structural and Seismological Settings Of The Area And The Mesupporting
confidence: 89%
“…The North Giudicarie system is an important segment of the Periadriatic lineament, the tectonic divide between the Alpine north-vergent collisional wedge and the South Alpine south-vergent thrust and fold belt. A sinistral kinematics along the North Giudicarie inferred from the focal mechanisms of this event would completely agree with a northwards indentation of the Adria microplate or promontory into the Eurasian plate (Bressan et al, 1998;Regenauer-Lieb and Petit, 1997;Renner and Slejko, 1994). Hence the importance to understand as exactly as possible the geometry of the fault plane of this earthquake.…”
Section: Introductionmentioning
confidence: 59%
“…The regional change in the tectonic style observed in central western Europe has been discussed by many authors and can be linked to: (a) variation in the force along the southern European boundary, due to irregular shape of the colliding continental margins (Illies, 1975;Regenauer-Lieb and Petit, 1997), (b) variation in the lithosphere strength of thermal origin (Grünthal and Stromeyer, 1992;Müller et al, 1997), (c) mechanical decoupling between crust and lithospheric mantle, allowing crustal fragments to move independently of each other Garcia-Castellanos et al, 2000). On the other hand, tomography studies (Granet et al, 1995a;Marquering and Sneider, 1996;Bijwaard et al, 1998) showed significant velocity variations under central western Europe.…”
Section: Discussionmentioning
confidence: 99%
“…For instance Lake Baikal results from the indentation of Asia by India (e.g. Tapponnier & Molnar, 1976), and the Eifel volcanic zone would result from the Alpine-European indentation (Regenauer & Petit, 1997 R approximately) may be invoked to a first order to assess whether a magmatic chamber is deep enough to generate a secondary magmatic reservoir very close to the surface. This speculative process requires a systematic investigation of double sources below volcanoes worldwide (e.g.…”
Section: Insights From the Modeled Failure Geometrymentioning
confidence: 99%